2013
DOI: 10.4067/s0718-34292013000400005
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest quality and shelf life of green pepper (Capsicum annuum L.) grown under open-field and greenhouse conditions

Abstract: In order to assess the influence of two production systems on postharvest quality and shelf life of two green pepper hybrids (Capsicum annuum L.), Anaheim-types 'Cardon' (mild hot) and '118' (mid hot), two experiments were carried out. In the first, plants were grown in open-field, and in the second under greenhouse conditions (soil directly and soilless). From each production system, fifty freshly harvested fruits were picked and stored at 20 ºC during 14 days. Weight loss, color analysis measured as lightnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Collectively, our data highlighted that red pepper can be considered as a good source of iron and potassium while red onion can be considered as a good source of zinc, sodium, and calcium. Consequently, the study confrms that the health beneft of spices may be attributed to the mineral element contents; these elements are useful as metabolism enhancer and antiallergen in the digestion system [33].…”
Section: Mineral Contentmentioning
confidence: 93%
“…Collectively, our data highlighted that red pepper can be considered as a good source of iron and potassium while red onion can be considered as a good source of zinc, sodium, and calcium. Consequently, the study confrms that the health beneft of spices may be attributed to the mineral element contents; these elements are useful as metabolism enhancer and antiallergen in the digestion system [33].…”
Section: Mineral Contentmentioning
confidence: 93%
“…On the other hand, Collins et al (1995) report values of 216 345 SHU for jalapeño pepper (C. annuum L.), which surpasses that reported by Orellana-Escobedo et al (2013) in nuts of this same type of chili, however, are lower than the maximum values found in this study. The high inter-and intraspecific variation, in relation to the synthesis and concentration of capsaicinoids, can be linked according to Wahyuni et al (2013) and Rodríguez-Uribe et al (2014) to the significant effect of the interaction of the fruit with the prevailing environment during the final stages of its growth and development, conditions that are mainly associated with environmental temperature and shading level (Jiménez et al, 2013), as well as to the state of maturity (Orellana-Escobedo et al, 2013) and to the extraction method used (Sánchez-Sánchez et al, 2010).…”
Section: Capsaicinoidsmentioning
confidence: 99%
“…Additionally, Fox et al (2005) reported values of 6.9 and 7.9 °Brix in fruits with ripeness of pepper consumption 'Robusta' and two harvest dates. The process of fruit maturation involves a series of changes related to respiration, degradation of compound such as chlorophyll and substances involved in obtaining cellular energy (Beckles, 2012), and its variation is widely correlated to its nutritional management (Yamamoto et al, 2013), variety and state of maturity (Jiménez et al, 2013).…”
Section: Total Soluble Solidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ωστόσο, η περιεκτικότητα όλων αυτών των βιοδραστικών ενώσεων στους καρπούς πιπεριάς καθορίζεται από διάφορους παράγοντες, όπως ο γενότυπος, οι περιβαλλοντικές συνθήκες κατά τη διάρκεια της καλλιέργειας, το στάδιο ωρίμανσης των καρπών κατά τη συγκομιδή, διάφορες καλλιεργητικές πρακτικές, καθώς και η διαχείριση των καρπών μετά τη συγκομιδή και πριν την κατανάλωση (Deepa et al, 2007;Ghasemnezhad et al, 2011;León et al, 2013;Martí et al, 2011;Russo & Howard, 2002b). Αξίζει να σημειωθεί ότι παρατηρούνται σημαντικές μεταβολές στην περιεκτικότητα των βιοδραστικών ενώσεων κατά τη διαδικασία ωρίμανσης του καρπού.…”
Section: B C Dunclassified